(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2025)
This article examines the strategies for enhancing the development of dialogic speech in primary school students through the implementation of a variative approach. The study highlights the use of flexible, interactive, and student-centered teaching methods, including group discussions, role-plays, problem-solving tasks, and game-based activities, to promote students’ communicative competence and active participation. Emphasis is placed on methodological planning, teacher preparedness, and the creation of a supportive learning environment as key factors for successful implementation. The research demonstrates that enhancing dialogic speech through a variative approach contributes to students’ linguistic, cognitive, and socio-emotional development, fostering creativity, critical thinking, and the ability to express ideas confidently.